Accelerating access to climate-smart innovations through private-sector-led scaling partnerships in Ghana - Mahama, Obed Kwaku; Obeng Adomaa, Faustina; Dalaa, Mustapha Alasan; Tepa Yotto, Ghislain; Kenfack-Essougong, Urcil Papito (2025)
This report highlights the bundled CIS-CSA solutions co-developed with scaling accelerator partners, the implementation of scaling activities, and the outcomes achieved in reaching 803,904 farmers in Ghana. Four accelerator consortia were formed: Smart Seed Packs and Market Systems for Smallholder Farmers; Solar Irrigation Solutions for Women Farmers; Climate-Smart Integrated Pest Management; and Smart Productions and Soils. Each consortium has the capacity to scale the bundled CIS-CSA solutions to farmers. Their offerings include Climate Information Services (CIS) and advisories, Climate-Smart Agriculture (CSA), financial solutions, market information, and decision support tools.